A high-sphericity, wide-sintering-window polymer powder material and a preparation method thereof
Patent Information
- Application Number
- CN202311371441.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-10-23
AI Technical Summary
但是,目前这些材料也主要通过粉碎方法进行制备(ACSAppliedMaterials&Interfaces,2021,13,41723),存在粉末流动性差、烧结窗口窄等问题
[0034] (1) The method of the present invention introduces a high-temperature annealing step near the melting point after melt extrusion. By controlling the annealing temperature and annealing time, the initial crystallization temperature and initial melting temperature of the polymer powder can be effectively controlled at the same time, so as to obtain a polymer powder material with a wider sintering window.
Smart Images

Figure CN117362978B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a polymer powder material with high sphericity and wide sintering window and its preparation method, belonging to the field of polymer additive manufacturing. Background Technology
[0002] Powder bed laser melting (PBF-LB / P) technology in additive manufacturing is a digital and personalized intelligent processing technology based on powder. In the polymer field, PBF technology (such as selective laser sintering, SLS) typically uses polymer powders with an average particle size of 30–150 μm as feedstock, employing lasers such as CO2, CO, or fiber semiconductors for layer-by-layer melting and sintering. This allows for the fabrication of high-precision, high-performance, and structurally complex three-dimensional polymer parts. PBF-LB / P technology usually requires the powder to be crystalline to ensure sufficient surface precision and mechanical properties in the finished product. Semi-crystalline long-chain polyamide materials (such as PA12, PA11, and their composite modified materials) have a large sintering window (SW, initial melting temperature T). m-onset With the initial crystallization temperature T c-onset With advantages such as a temperature difference ≥25~30℃, low viscosity, low water absorption, and outstanding mechanical properties, these long-chain polyamide materials are currently the main raw materials for PBF-LB / P technology. However, the resins and powders of these materials are relatively expensive, and sintered products often suffer from drawbacks such as low reusability and poor solvent resistance. Therefore, it is urgent to broaden the sources of polymer powder raw materials suitable for PBF-LB / P technology.
[0003] Polypropylene (PP) is one of the most widely used and cheapest general-purpose plastics, especially in consumer sectors such as automobiles. Using PP as a powder raw material allows for the production of products with materials essentially identical to those used in existing automotive parts, which is significant for expanding the application of PBF-LB / P technology in these fields. PP materials do not suffer from the post-condensation aging problems common in polyamides, and the powder has a high reusability rate, which helps reduce production costs. Homopolymer PP, polymerized from a single propylene monomer, generally has a high crystallization temperature, a fast crystallization rate, and a large shrinkage rate. Although there are a few reports of homopolymer PP powder products on the market, due to the aforementioned crystallization issues, it is expected to cause severe warping problems during printing, thus making it impossible to mold large-size products (Additive Manufacturing 2021, 37, 101610).
[0004] Currently, commercially available PP powders prepared using existing technologies (such as BASF's UltrasintNat 01) are all copolymer PP. Copolymer PP incorporates a small amount (1-20%) of comonomers such as ethylene into its molecular chain to reduce the regularity of the PP molecular chain, delay crystallization, and reduce shrinkage caused by crystallization. However, the melting peak of copolymer PP powders prepared using existing technologies is typically broad, and the powder is prone to agglomeration during preheating. Furthermore, these copolymer PP powders also have relatively high crystallization temperatures, resulting in a narrow sintering window and a tendency for warping in the finished product. Some patents (such as CN111511823A) propose annealing the PP resin or powder within a narrow temperature range below its melting point, which can increase the initial melting temperature to some extent, but it cannot effectively control the initial crystallization temperature of the powder. Patent CN109291302A proposes treating semi-crystalline powder in a high-temperature organic solvent to expand the sintering window to 14.9℃, but this still falls short of commercial powder standards and requires the use of an organic solvent. More importantly, existing PP powder preparation technologies mainly rely on cryogenic grinding (cooling PP resin below its embrittlement temperature) (e.g., CN113004622A) and other forms of mechanical grinding (e.g., CN107825621A). Powder particles obtained through mechanical grinding (also known as solid-phase grinding) generally exhibit irregular shapes, wide particle size distributions, poor flowability, and low bulk density (~0.3 g / cm³). 3 Problems such as these lead to poor performance of the sintered parts. Some existing spheroidization technologies (e.g., CN107825621A, CN108501250B, CN113146881A, CN114262518A, etc.) propose to transform irregularly shaped pulverized powder into near-spherical powder by heating in the liquid or gas phase. However, these methods generally suffer from low efficiency, low yield, easy powder degradation, and difficulty in washing, which undoubtedly greatly increases the cost of powder production. These powders, due to the presence of many heterogeneous nucleating substances in the resin itself or the introduction of various nucleating impurities during pulverization, typically have relatively high crystallization temperatures and narrow sintering windows. A few studies and patents (such as CN201610258564.4, Journal of Polymer Science Part B: Polymer Physics, 2017, 55, 4, 320-329, etc.) utilize the dissolution-precipitation method (also known as the liquid-phase method) widely used in polyamide powder preparation to prepare PP powder with a wide sintering window through the principle of solution phase separation. However, these powders usually have a loose and porous structure, and the preparation process requires the use of toxic solvents such as toluene, posing environmental problems.
[0005] In addition, materials such as polyvinylidene fluoride (PVDF) have advantages such as suitable sintering temperature and high reusability, and are also potential materials in the PBF-LB / P field. However, at present, these materials are mainly prepared by pulverization method (ACS Applied Materials & Interfaces, 2021, 13, 41723), which has problems such as poor powder flowability and narrow sintering window.
[0006] The polymer powders currently prepared have problems such as large particle size, uneven particle size, high crystallization temperature, narrow sintering window, or poor environmental performance due to the introduction of toxic solvents in the preparation process, which are not conducive to their application in technologies such as PBF-LB / P. Summary of the Invention
[0007] To address the aforementioned deficiencies, this invention provides a polymer powder material with high sphericity and a wide sintering window, along with its preparation method. This invention uses polymer granules, water-soluble polymer granules, and antioxidants as raw materials. First, the raw materials are mixed and then melt-extruded to obtain a blend with the target polymer as the dispersed phase and the water-soluble polymer as the continuous phase. Then, the blend is annealed for a specific time at a temperature close to the melting point of the polymer granules. The annealed product is then dissolved in hot water, washed, separated, and dried to obtain a polymer powder material with high sphericity, narrow particle size distribution, a wide sintering window, and a relatively environmentally friendly preparation process. By annealing the melt-extruded blend at a temperature close to its melting point, this invention effectively reduces the initial crystallization temperature and increases the initial melting temperature of the powder, thereby significantly widening the sintering window of the polymer powder.
[0008] The technical solution of the present invention:
[0009] The first technical problem to be solved by the present invention is to provide a method for preparing a polymer powder material, the method comprising the following steps:
[0010] A. A composite granule is obtained by uniformly mixing a polymer granule, a water-soluble polymer, and an antioxidant; wherein the polymer granule is selected from crystalline polymers such as polypropylene, polyvinylidene fluoride, polyoxymethylene, polyamide, or polyester.
[0011] B. The composite granules are melt-extruded to obtain a blend with polymer granules as the dispersed phase and water-soluble polymer as the continuous phase;
[0012] C. Anneal the blend, wherein the annealing temperature is (T-10)~(T+20)℃, where T is the melting point of the polymer granules described in step A, and the annealing time is 1~2.5 hours;
[0013] D. After cooling the annealed blend, dissolve it in water to obtain a suspension containing polymer powder;
[0014] E. The suspension is filtered and washed multiple times, and finally dried and sieved to obtain the polymer powder material.
[0015] Furthermore, in step A, the proportions of the polymer granules, water-soluble polymer, and antioxidant are: 90-120 parts by weight of polymer granules, 200-400 parts by weight of water-soluble polymer, and 1-10 parts by weight of antioxidant.
[0016] Further, in step A, the water-soluble polymer is selected from polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, water-soluble polyester, or oligosaccharides, etc. Preferably, the selected polyethylene glycol has a molecular weight of 10. 4 ~10 5 Between g / mol.
[0017] Furthermore, the mass ratio of the water-soluble polymer to the polymer granules is 10:90 to 90:10.
[0018] Further, in step A, the antioxidant includes a primary antioxidant and a secondary antioxidant. The primary antioxidant is selected from hindered phenolic antioxidants, lactone-type antioxidants, thiobisphenol antioxidants, or hydroxylamine antioxidants. The secondary antioxidant is selected from phosphite antioxidants or organosulfur antioxidants. The mass ratio of the primary antioxidant to the secondary antioxidant is 1:1 to 4.
[0019] Furthermore, in step A, reinforcing agents, toughening agents, radiation absorbers, thermally conductive media, etc., can be added to the polymer granules to improve the sintering performance and mechanical properties of the polymer powder.
[0020] Furthermore, in step A, before the polymer granules are blended with the water-soluble polymer and antioxidant, they can be subjected to an antioxidant stabilization modification treatment. The method of the antioxidant stabilization modification treatment is as follows: the polymer granules and antioxidant are melt-extruded and granulated, and the mass ratio of polymer granules to antioxidant is 90-120:0.5-5.
[0021] Furthermore, the antioxidant includes a primary antioxidant and a secondary antioxidant. The primary antioxidant is selected from hindered phenolic antioxidants, lactone-type antioxidants, thiobisphenol antioxidants, or hydroxylamine antioxidants. The secondary antioxidant is selected from phosphite antioxidants or organosulfur antioxidants. The mass ratio of the primary antioxidant to the secondary antioxidant is 1:1 to 4.
[0022] Furthermore, in step B, the extrusion temperature is 190–210°C and the screw speed is 60–120 rpm.
[0023] Furthermore, in step D, the temperature of the water used is between 50 and 100°C.
[0024] Furthermore, the weight ratio of water to the annealed blend is 1 to 10:1.
[0025] Furthermore, in step E, the filtration process specifically involves: filtering the suspension using a filter screen with a mesh size of 300 to 600; and washing the suspension a number of times or more than 3.
[0026] The second technical problem to be solved by the present invention is to provide a polymer powder material, which is prepared by the above method.
[0027] Furthermore, the sintering window of the powder material is 25–40°C.
[0028] Furthermore, the sphericity of the powder material is ≥0.93.
[0029] The third technical problem to be solved by the present invention is to point out the application of the above-mentioned polymer powder materials in powder bed laser melting technology, high-speed thermal sintering or multi-jet melting and other powder bed melting additive technologies.
[0030] The fourth technical problem to be solved by this invention is to provide a method for broadening the sintering window of polymer powder and reducing the crystallization temperature of polymer powder. The method is as follows: using polymer granules, water-soluble polymers and antioxidants as raw materials, polymer powder is prepared sequentially through raw material blending, melt extrusion, annealing, suspension preparation and post-treatment; wherein, the annealing temperature is (T-10)~(T+20)℃, T is the melting point of the polymer granules used, and the annealing time is 1~2.5 hours; the polymer granules are selected from crystalline polymers such as polypropylene, polyvinylidene fluoride, polyoxymethylene, polyamide or polyester.
[0031] Furthermore, the preparation of the suspension refers to: cooling the annealed blend and adding it to water to obtain a suspension containing polymer powder.
[0032] Furthermore, the post-processing refers to: filtering and washing the suspension multiple times, and finally drying and sieving to obtain polymer powder.
[0033] The beneficial effects of this invention are:
[0034] (1) The method of the present invention introduces a high-temperature annealing step near the melting point after melt extrusion. By controlling the annealing temperature and annealing time, the initial crystallization temperature and initial melting temperature of the polymer powder can be effectively controlled at the same time, so as to obtain a polymer powder material with a wider sintering window.
[0035] (2) The method of the present invention reduces the residual amount of water-soluble polymers on the powder surface to a large extent by washing the powder multiple times, which is beneficial to improving the high-temperature fluidity of the powder and avoiding the problem of powder agglomeration.
[0036] (3) The method of the present invention adds antioxidants in the material modification, melt extrusion and flow modification processes, which greatly reduces the possibility of powder degradation during the preparation and sintering processes, and is conducive to improving the reusability of powder and the mechanical properties of sintered products.
[0037] (4) The powder material prepared by the present invention has the advantages of wide sintering window (25-40℃), high sphericity, adjustable particle size, narrow particle size distribution, good high temperature fluidity, high bulk density, and high reusability.
[0038] (5) The method of the present invention has the advantages of good universality, easy implementation, and environmentally friendly process (using water as a solvent). It is not only applicable to polypropylene powder, but also to the preparation of crystalline powders such as polyvinylidene fluoride, polyoxymethylene, polyamide, and polyester.
[0039] The term “initial crystallization temperature” as used in this article refers to the temperature or temperature range at which molten amorphous material transforms into crystalline material upon cooling.
[0040] The term “initial melting temperature” as used herein refers to the temperature or range at which a substance, preferably a homopolymer, copolymer, or blend of polymers, transitions from a solid to a liquid state.
[0041] The term "sintering window" as used in this article refers to the temperature range between the initial crystallization temperature and the initial melting temperature. Attached Figure Description
[0042] Figure 1 The morphology and particle size distribution of the polypropylene powder prepared in Example 1 are shown.
[0043] Figure 2 The DSC curves are used to compare the crystallization and melting behavior of the polypropylene powder and resin prepared in Example 1. Detailed Implementation
[0044] This invention provides a polymer powder material with high sphericity and a wide sintering window, and its preparation method. The invention uses polymer granules, water-soluble polymer granules, and antioxidants as raw materials. These raw materials are first mixed and then melt-extruded. Following melt extrusion, a high-temperature annealing step near the melting point is introduced. By controlling the annealing temperature and time, the initial crystallization temperature and initial melting temperature of the polymer powder are effectively controlled, resulting in a powder material with a wide sintering window. The obtained polymer powder material exhibits high sphericity, narrow particle size distribution, and a wide sintering window.
[0045] Unless otherwise specified, all parts in this invention refer to parts by weight.
[0046] The following is in conjunction with the appendix Figure 1 , 2The present invention will be further described in detail with reference to corresponding embodiments and comparative examples, so that those skilled in the art can implement it based on the description.
[0047] Example 1:
[0048] The blend was prepared by mixing and extrusion. 100 parts of copolymer PP (Moplen RP340R, melting point 146℃) and 0.5 parts of antioxidant (antioxidant 1010: antioxidant 168 = 1:2) were mixed and modified in a high-speed mixer to obtain modified copolymer PP. Then, the following steps were performed:
[0049] A. Mix 100 parts of modified copolymer PP and 300 parts of polyethylene glycol (molecular weight 2×10⁻⁶). 4 The composite granules were obtained by thoroughly mixing (g / mol) and 2 parts antioxidant (antioxidant 1010: antioxidant 168 = 1:2) in a high-speed mixer;
[0050] B. The composite granules are extruded using a twin-screw extruder at an extrusion temperature of 200℃ and a screw speed of 120rpm to obtain a blend containing PP particles;
[0051] C. Place the blend in a vacuum oven and anneal it at 140°C (close to the resin melting point) for 1 hour under nitrogen protection;
[0052] D. Cool the annealed blend and dissolve it in twice the volume of water to obtain a suspension containing PP spherical powder;
[0053] E. The suspension is filtered and washed three times, and finally dried and sieved at 80°C to obtain PP powder with high sphericity;
[0054] F. Mix 100 parts of spherical powder with 0.1 parts of SiO2 nanoparticle flow aid (Degussa R974) and 0.5 parts of antioxidant (antioxidant 1010: antioxidant 168 = 1:2) to obtain sintered powder raw material suitable for PBF-LB / P technology.
[0055] The prepared powder was characterized by scanning electron microscopy, and the results are as follows: Figure 1 This indicates that the obtained sample is spherical in shape and has a particle size in the micrometer range.
[0056] The flowability parameters of the powder were characterized using a powder rheology instrument. Table 1 compares the flow properties of the unmodified polypropylene powder (PP) prepared in Example 1 with those of commercially available PP powder (iCoPP), including the avalanche angle (α). A The angle (f) represents the resistance to powder flow, primarily due to friction between particles. A smaller angle means the powder flows more easily. Standard deviation (f) AAvalanche fractal is a measure of the uniformity and consistency of flow, with lower values indicating more controlled behavior. Avalanche fractal quantifies the smoothness of the powder surface after an avalanche. Hausner ratio (HR) is defined as the ratio between the powder's packing free flow density and its tap density. Generally, powders with a Hausner ratio < 1.25 are considered to have good flowability and are suitable for selective laser sintering (SLS). Table 1, comparing with commercial powders, shows that the powder prepared using this method exhibits excellent flow properties.
[0057] Table 1. Comparison of the flow properties of the polypropylene powder prepared in Example 1 and commercial PP powder.
[0058]
[0059] Table 2 shows the particle size distribution and particle shape parameters of the powder in Example 1. From Table 2, it can be seen that the elliptic smoothness σ... E Defined as the ratio between the perimeter of a particle and the perimeter of the fitted ellipse around it, this characterizes the regularity of the particle surface; the closer the ellipse smoothness is to 1, the smoother the particle surface. Particle sphericity S (the ratio between the surface area of the particle and its surrounding convex hull) further defines the particle shape; the higher the sphericity, the rounder the particle. Aspect ratio A (the ratio of the particle's length to its width) characterizes whether the particle has an isotropic shape; the closer the aspect ratio is to 1, the more isotropic the particle shape. Table 2 concludes that the powder obtained by our method has high sphericity and a narrow particle size distribution.
[0060] Table 2. Particle size distribution and particle shape parameters of the powder in Example 1.
[0061]
[0062] Example 2:
[0063] Compared with Example 1, the difference lies in the annealing temperature: in step C, the blend is placed in a vacuum oven and annealed for 1 hour at 150°C, which is higher than the melting point of the resin, under nitrogen protection.
[0064] Example 3:
[0065] The difference compared to Example 1 lies in the annealing time:
[0066] In step C, the blend is placed in a vacuum oven and annealed for 2 hours at 140°C, close to the melting point of the resin, under nitrogen protection.
[0067] Example 4:
[0068] The difference compared to Example 1 lies in the annealing time:
[0069] In step C, the blend is placed in a vacuum oven and annealed for 2.5 hours at 140°C, close to the melting point of the resin, under nitrogen protection.
[0070] Example 5:
[0071] Compared to Example 1, the difference lies in the material used, which is polyvinylidene fluoride (PVDF), and the annealing temperature.
[0072] In step C, the blend is placed in a vacuum oven and annealed for 1 hour at 160°C, close to the melting point of PVDF resin, under nitrogen protection.
[0073] Comparative Example 1:
[0074] The difference from Example 1 is that the annealing process in step C is omitted.
[0075] Comparative Example 2:
[0076] The difference compared to Example 1 lies in the annealing temperature.
[0077] In step C, the blend is placed in a vacuum oven and annealed for 1 hour at 130°C, below the melting point of the powder, under nitrogen protection.
[0078] Comparative Example 3:
[0079] The difference compared to Example 1 lies in the annealing temperature:
[0080] In step C, the blend is placed in a vacuum oven and annealed for 1 hour at 160°C, which is higher than the melting point of the resin, under nitrogen protection.
[0081] Comparative Example 4:
[0082] The difference compared to Example 1 lies in the annealing time:
[0083] In step C, the blend is placed in a vacuum oven and annealed for 0.5 hours at 140°C, close to the melting point of the resin, under nitrogen protection.
[0084] Comparative Example 5:
[0085] The difference compared to Example 2 lies in the annealing time:
[0086] In step C, the blend is placed in a vacuum oven and annealed for 3 hours at 150°C, which is higher than the melting point of the resin, under nitrogen protection.
[0087] Comparative Example 6:
[0088] Compared with Example 1, the difference is that step C is omitted, but the powder is annealed at 140°C, close to the melting point of the resin, for 1 hour after washing and drying.
[0089] Comparative Example 7:
[0090] Compared to Example 5, the difference is that the annealing process in step C is omitted.
[0091] Comparative Example 8:
[0092] Compared with Example 5, the difference is that step C is omitted, but the powder is annealed at 160°C, close to the melting point of the resin, for 1 hour after washing and drying.
[0093] Table 3. Size and crystallinity of powders obtained in the examples and comparative examples.
[0094]
[0095]
[0096] The initial crystallization temperature and initial melting temperature of the powder were characterized by differential scanning calorimetry (DSC), and the corresponding sintering window was calculated. The average particle size of the powders obtained in each embodiment and comparative example was characterized by laser particle size analyzer. The results are shown in Table 3.
[0097] As can be seen from the table above, this invention successfully prepared a polypropylene powder material with a large sintering window and suitable size and morphology, applicable to powder bed melting technology. Specifically, comparing Example 1 with Comparative Example 1, it can be seen that near-melting-point annealing of the extruded blend effectively lowers the initial crystallization temperature (by 7.2°C) and increases the initial melting temperature (by 2.6°C), thereby achieving a sintering window (26.1°C) comparable to that of polyamide powder while maintaining essentially the same or only slightly increasing the powder size. Examples 2-4 show that appropriately increasing the annealing temperature or extending the annealing time can enhance the annealing effect, obtaining a larger sintering window, while maintaining essentially the same or only slightly increasing the powder size. Comparative Examples 2-5 show that excessively low / high annealing temperatures and excessively short / long annealing times will result in insignificant or even no annealing effect (i.e., no significant widening of the sintering window), and in some cases, even severe agglomeration of the powder, leading to a significant increase in particle size. Compared with Comparative Example 6, Example 1 shows that high-temperature near-melting-point annealing of the powder washed and dried from the unannealed blend does not lead to a significant widening of the sintering window. Examples 5 and Comparative Examples 7-8 demonstrate that this method is not only applicable to polypropylene, but also has a similar effect in crystalline resins such as polyvinylidene fluoride (PVDF).
Claims
1. A method for preparing a polymer powder material, characterized in that, The method includes the following steps: A. A composite granule is obtained by uniformly mixing polymer granules, water-soluble polymer, and antioxidant; wherein the polymer granules are selected from polypropylene, polyvinylidene fluoride, polyoxymethylene, polyamide, or polyester; the ratio of polymer granules, water-soluble polymer, and antioxidant is: 90-120 parts by weight of polymer granules, 200-400 parts by weight of water-soluble polymer, and 1-10 parts by weight of antioxidant. B. The composite granules are melt-extruded to obtain a blend with polymer granules as the dispersed phase and water-soluble polymer as the continuous phase; C. Anneal the blend, wherein the annealing temperature is (T-10) ~ (T+20)℃, where T is the melting point of the polymer granules described in step A, and the annealing time is 1~2.5 hours; D. After cooling the annealed blend, dissolve it in water to obtain a suspension containing polymer powder; E. The suspension is filtered and washed multiple times, and finally dried and sieved to obtain the polymer powder material.
2. The method for preparing a polymer powder material according to claim 1, characterized in that, In step A, the water-soluble polymer is selected from polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, water-soluble polyester, or oligosaccharides.
3. The method for preparing a polymer powder material according to claim 2, characterized in that, The selected polyethylene glycol has a molecular weight of 10. 4 ~10 5 Between g / mol.
4. The method for preparing a polymer powder material according to claim 1, characterized in that, The mass ratio of the water-soluble polymer to the polymer granules is 10:90 to 90:
10.
5. The method for preparing a polymer powder material according to claim 1 or 2, characterized in that, In step A, the antioxidant includes a primary antioxidant and a secondary antioxidant. The primary antioxidant is selected from hindered phenolic antioxidants, lactone-type antioxidants, thiobisphenol antioxidants, or hydroxyamine antioxidants. The secondary antioxidant is selected from phosphite antioxidants or organosulfur antioxidants. The mass ratio of the primary antioxidant to the secondary antioxidant is 1:1 to 4.
6. The method for preparing a polymer powder material according to claim 1 or 2, characterized in that, In step A, at least one of a reinforcing agent, a toughening agent, an irradiation absorber, or a thermally conductive medium is added to the polymer granules.
7. The method for preparing a polymer powder material according to claim 1 or 2, characterized in that, In step A, before the polymer granules are blended with the water-soluble polymer and antioxidant, they are first subjected to antioxidant stabilization modification treatment. The method of antioxidant stabilization modification treatment is as follows: the polymer granules and antioxidant are melt-extruded and granulated, and the mass ratio of polymer granules to antioxidant is 90~120:0.5~5.
8. The method for preparing a polymer powder material according to claim 1 or 2, characterized in that, In step B, the extrusion temperature is 190~210℃ and the screw speed is 60~120 rpm; In step D, the temperature of the water used is between 50 and 100°C; The weight ratio of water to the annealed blend is 1 to 10:1; In step E, the filtration process specifically involves: filtering the suspension using a filter screen with a mesh size of 300 to 600; and washing the suspension three or more times.
9. A polymer powder material, characterized in that, The powder material is prepared by the method described in any one of claims 1 to 8.
10. The application of polymer powder materials in powder bed laser melting technology, high-speed thermal sintering, and multi-jet melting, characterized in that, The polymer powder material is a polymer powder material prepared by the method described in any one of claims 1 to 8, or a polymer powder material as described in claim 9.
11. A method for broadening the sintering window of polymer powder and lowering the crystallization temperature of polymer powder, characterized in that, The method is as follows: using polymer granules, water-soluble polymers, and antioxidants as raw materials, polymer powder is prepared sequentially through raw material blending, melt extrusion, annealing, suspension preparation, and post-treatment; wherein, the annealing temperature is (T-10) ~ (T+20)℃, where T is the melting point of the polymer granules used, and the annealing time is 1~2.5 hours; the polymer granules are selected from polypropylene, polyvinylidene fluoride, polyoxymethylene, polyamide, or polyester; the ratio of polymer granules, water-soluble polymers, and antioxidants is: 90~120 parts by weight of polymer granules, 200~400 parts by weight of water-soluble polymers, and 1~10 parts by weight of antioxidants.
12. The method for broadening the sintering window of polymer powder and reducing the crystallization temperature of polymer powder according to claim 11, characterized in that, The preparation of the suspension refers to adding the annealed blend to water after cooling to obtain a suspension containing polymer powder.
13. The method for broadening the sintering window and lowering the crystallization temperature of polymer powder according to claim 11, characterized in that, The post-processing refers to: filtering and washing the suspension multiple times, and finally drying and sieving to obtain polymer powder.
Citation Information
Patent Citations
Polypropylene powder for selective laser sintering and preparation thereof
CN107304251A
Polymer-based micron / nano functional composite spherical powder and preparing method thereof
CN107825621A
Gas flow spheroidizing reactor and method for preparing polymer-based spherical powder materials
CN108501250B
Widening method of semi-crystalline polymer powder sintering window
CN109291302A
Fluoropolymer powder having extended sintering window using heat treatment, and use thereof in laser sintering
CN111511823A